Emergency Department waiting-time in the post pandemic era: new organizational models, a challenge for the future - Stirparo, Giuseppe; Kacerik , Erika; Andreassi, Aida; Pausilli, Paolo; Cortellaro, Francesca; Coppo, Anna; Migliari, Maurizio; Albonico, Andrea; Sechi, Giuseppe Maria; Zoli, Alberto; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Covid-19 has profoundly changed the Emergency Department system in Lombardy, especially for the type of accesses and the number of diagnoses. Accordingly, the pre-hospital rescue system has undergone heavy changes, in particular regarding the times of rescue. Despite this, studies concerning the post-pandemic phase are lacking to understand whether the conditions of the emergency systems has resumed to the pre-pandemic period. The aim of the study is to evaluate the length of stay (LOS) phenomenon in the emergency departments (EDs) in the post-pandemic era.Methods: a retrospective observational study was conducted, which analyzed the first six months of the years 2019, 2021 and 2022. The pandemic peak phase, corresponding to the first months of 2020, wasn’t included. The investigated area included the provinces of Milan and Monza, a metropolitan area with 4 million inhabitants.Results: The average time spent by patients in the ED increased by +3.8 hours in 2022 and by +1.3 hours in 2021 compared to 2019. The average time from ED access to hospitalization also increased by +4.8 hours in 2022 and +5.0 hours in 2021 compared to 2019. The percentage of time in ED recorded in a National Emergency Department Overcrowding Study (NEDOCS) in black code in 2022 reached 5.4% against 1.7% in 2021 and 0.5 % in 2019.Conclusions: data show an increase in the time spent in the EDs and an increase in the overcrowding, according to the NEDOCS index. New management models and a reorganization of EDs are needed as the workload has increased significantly.